Endogenous, tissue-resident stem/progenitor cells in gonads and bone marrow express FSHR and respond to FSH via FSHR-3 - Deepa Bhartiya; Hiren Patel; Ankita Kaushik; Pushpa Singh; Diksha Sharma (BMC, 2021)
Abstract Follicle stimulating hormone (FSH) is secreted by the anterior pituitary and acts on the germ cells indirectly through Granulosa cells in ovaries and Sertoli cells in the testes. Extragonadal action of FSH has been reported but is still debated. Adult tissues harbor two populations of stem cells including a reserve population of primitive, small-sized, pluripotent very small embryonic-like stem cells (VSELs) and slightly bigger, tissue-specific progenitors which include ovarian stem cells (OSCs) in ovaries, spermatogonial stem cells (SSCs) in testes, endometrial stem cells (EnSCs) in uterus and hematopoietic stem cells (HSCs) in the bone marrow. Data has accumulated in animal models showing FSHR expression on both VSELs and progenitors in ovaries, testes, uterus and bone marrow and eventually gets lost as the cells differentiate further. FSH exerts a direct action on the stem/progenitor cells via alternatively spliced FSHR-3 rather than the canonical FSHR-1. FSH stimulates VSELs to undergo asymmetrical cell divisions to self-renew and give rise to the progenitors that in turn undergo symmetrical cell divisions and clonal expansions followed by differentiation into specific cell types. Excessive self-renewal of VSELs results in cancer and this explains ubiquitous expression of embryonic markers including nuclear OCT-4 along with FSHR in cancerous tissues. Focus of this review is to compile published data to support this concept. FSHR expression in stem/progenitor cells was confirmed by immuno-fluorescence, Western blotting, in situ hybridization and by quantitative RT-PCR. Two different commercially available antibodies (Abcam, Santacruz) were used to confirm specificity of FSHR expression along with omission of primary antibody and pre-incubation of antibody with immunizing peptide as negative controls. Western blotting allowed detection of alternatively spliced FSHR isoforms. Oligoprobes and primers specific for Fshr-1 and Fshr-3 were used to study these alternately-sliced isoforms by in situ hybridization and their differential expression upon FSH treatment by qRT-PCR. To conclude, stem/progenitor cells in adult tissues express FSHR and directly respond to FSH via FSHR-3. These findings change the field of FSH-FSHR biology, call for paradigm shift, explain FSHR expression on cancer cells in multiple organs and provide straightforward explanations for various existing conundrums including extragonadal expression of FSHR.